Toxoplasma gondii induces MST2 phosphorylation mediating the activation of hippo signaling pathway to promote apoptosis and lung tissue damage - Kangzhi Xu; Shifan Zhu; Fan Xu; Jin Yang; Bin Deng; Dingzeyang Su; Jing Ma; Mingyue Zu; Yifan Lin; Tianxu Pei; Yuyang Zhu; Lele Wang; et al. (iScience)
Summary: Toxoplasma gondii (T. gondii) is an intracellular parasite, and its regulation of host cell apoptosis directly affects its parasitism. Studies link T. gondii-induced apoptosis to abnormal expression of mammalian STE20-like protein kinase 2 (MST2), but its precise role remains unclear. In this study, the regulatory roles in apoptosis and pathogenicity of T. gondii infection were identified in vitro and in vivo. Simultaneously, MST2 and Hippo signaling pathway activation induced by T. gondii were evaluated. MST2 overexpression and knockout were used to assess its regulatory role in apoptosis and Hippo signaling pathway. Results showed that T. gondii induced apoptosis and lung damage, with Hippo signaling pathway activation via MST2 phosphorylation. MST2 was demonstrated to regulate apoptosis and Hippo signaling pathway. Notably, MST2 knockout hindered the T. gondii-induced apoptosis and weakened Hippo signaling pathway activation. MST2 is an important target for T. gondii to control host cell fate and modulate immune responses.